(untitled) (Asian Journal of Medical and Biological Research, 2020)
The research was aimed to determine the present status of probiotics (Lactobacillus spp.) and pathogenic bacteria (Vibrio spp.) of culture pond as well as to determine whether the isolated probiotic Lactobacillus spp. can act as a controlling agent on experimentally pathogenic Vibrio spp. infected Penaeus monodon. In In-vitro test of gills and intestinal tracts, the potential antagonistic activity of Lactobacillus spp. toward Vibrio spp. was gradually observed at 4th hour of probiotic treatment. At 12th hour the viable count of Vibrio spp. was drastically reduced in gill from 2.33×105 to 1.03×103 (CFUg-1) and in intestinal tract 2.35×105 to 6.43×102 (CFUg-1). While, in In-vivo test, in case of muscle, gills and intestinal tract antagonistic activity of Lactobacillus spp. toward Vibrio spp. was noticed after 9 hours, 21 hours and 27 hours respectably of probiotic injected shrimps. However, only the result of in-vitro challenge test revealed that, Lactobacillus spp. significantly reduced the Vibrio spp. viable count of the gills of the selected samples (P=0.037). The investigation showed antagonistic effect of probiotic (Lactobacillus spp.) on experimentally Vibrio spp. infected shrimp. Asian J. Med. Biol. Res. June 2020, 6(2): 311-315